2023
DOI: 10.1186/s12879-023-08010-8
|View full text |Cite|
|
Sign up to set email alerts
|

The clinical outcomes of COVID-19 critically ill patients co-infected with other respiratory viruses: a multicenter, cohort study

Abstract: Background Previous studies have shown that non-critically ill COVID-19 patients co-infected with other respiratory viruses have poor clinical outcomes. However, limited studies focused on this co-infections in critically ill patients. This study aims to evaluate the clinical outcomes of critically ill patients infected with COVID-19 and co-infected by other respiratory viruses. Methods A multicenter retrospective cohort study was conducted for all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Another study of ours reported a longer hospital stay in the remaining mixed infections of SARS-CoV-2 with other respiratory viruses, as along with a greater percentage of intensive treatments [ 23 ]. A similar trend has been reported in other studies [ 24 ]. Furthermore, participants who were co-infected with SARS-CoV-2 and eHCoV had approximately threefold higher CRP and lower saturation levels than those co-infected with other respiratory viruses.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Another study of ours reported a longer hospital stay in the remaining mixed infections of SARS-CoV-2 with other respiratory viruses, as along with a greater percentage of intensive treatments [ 23 ]. A similar trend has been reported in other studies [ 24 ]. Furthermore, participants who were co-infected with SARS-CoV-2 and eHCoV had approximately threefold higher CRP and lower saturation levels than those co-infected with other respiratory viruses.…”
Section: Discussionsupporting
confidence: 92%
“…In a previous study conducted by us, it was reported that individuals who were infected with both SARS-CoV-2 and another respiratory virus had a more severe clinical course and required more frequent hospitalisation or invasive treatment [ 23 ]. Other studies have also reported a more severe clinical picture in patients with COVID-19 who were co-infected [ [24] , [25] , [26] ]. Based on laboratory findings, imaging studies, and disease outcomes, some authors showed that co-infections do not aggravate the condition of the patient [ 27 ].…”
Section: Introductionmentioning
confidence: 95%
“…This study is part of the Saudi Critical Care Pharmacy Research (SCAPE) platform, which conducted several studies that evaluated the safety and effectiveness of multiple therapies in critically ill patients ( 18 ). The design of this multicenter cohort study is similar to previously published studies ( 19 25 ). The details of the study design are available in Supplementary material .…”
Section: Methodsmentioning
confidence: 85%
“…As of March 2024, the number of confirmed COVID-19 cases has surpassed 770 million 1 . The wide spectrum of symptoms, varying from mild to severe respiratory distress and multi-organ dysfunction 2 , underscores the need for a comprehensive systemic understanding of the disease's pathophysiology and the factors contributing to its diverse clinical outcomes 3,4 . In addition to the immediate health impacts, the COVID-19 pandemic has highlighted the long-lasting effects and challenges in the post-recovery phase.…”
Section: Introductionmentioning
confidence: 99%